Sintilimab plus docetaxel as second-line therapy of advanced non-small cell lung cancer without targetable mutations: a phase II efficacy and biomarker study - Yongchang Zhang; Lianxi Song; Liang Zeng; Yi Xiong; Li Liu; Chunhua Zhou; Haiyan Yang; Zhan Wang; Qing Xia; Wenjuan Jiang; Qinqin Xu; Nong Yang (BMC Cancer, 2022)
Highlights • Survival outcomes of patients with NSCLC without targetable mutations remain depressing. • Sintilimab plus docetaxel as second-line therapy improves progression-free survival outcomes. • Sintilimab plus docetaxel is safe and well-tolerated. • Patients detected with high PD-L1 expression in circulating tumor cells (≥32.5%, median level in 30 patients) achieved significantly higher ORR, PFS and OS. • Patients detected with PD-L1 < 1% and CD8 ≥ 1% expression from their baseline tissue samples had significantly higher ORR (p = 0.026).